PARALLEL COMPUTING PLATFORM FOR EVALUATING LDPC CODES PERFORMANCE - Alghonaim, Esa (2007)
This paper presents a novel approach for the design and implementation of a simulation platform for evaluating LDPC codes performance. The existing LDPC code simulation tools consume very long time in evaluating the performance of a specific code design. This is due to the intensive number of required computations. This problem is overcome by developing a parallel protocol to distribute the computations among processing nodes in a TCP/IP network. As indicated by experimental results, the proposed simulation platform is scalable with the number of processing nodes. Another practical advantage of the proposed system is that it does not need dedicated processors to run it; rather, it can utilize idle times of processing nodes in a network and work transparent to a node user. Furthermore, network daemons are used to utilize network nodes even if they are in the log-off state.